Bibliometric Computational Mapping Analysis Using Vosviewer: A Review on Pedagogy for Early Childhood and Computer Science - Kuswanto, Kuswanto; Kama Abdul Hakam; Juntika Nurihsan; Cece Rakhmat; Nurul Fadillah; Syahriyati (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to examine the development of pedagogy research for early childhood and computer science using the bibliometric mapping analysis method with VOSviewer. Data collected from this research are articles that have been published and indexed by Google Scholar. Keywords such as “pedagogy”, “early childhood”, and “computer science” are used in performing data collection through the Publish or Perish (PoP) software application. 996 articles were obtained, ranging from 2012 to 2021 (10 year-time). The result of this research shows that the theme of pedagogy for early childhood and computer science fluctuated from 2012 to 2015. Meanwhile, it experienced a drastic decline in the past 6 years (2016-2021). From these results, there are three main research themes obtained, namely pedagogy (290 links, total link strength of 2444, and 377 occurrences), early childhood (228 links, total link strength of 752, and 102 occurrences), and computer science (254 links, total link strength of 1403, and 213 occurrences). Topics that tend to be frequently researched are pedagogy, science, technology, teacher, education, child, play, use, early childhood education, skills, school, and computer science. Hence, there are numerous research topics that should be explored, developed, and conducted. Therefore, the study of pedagogy for early childhood and computer science is possible to be developed in parallel with other research topics.